2018
DOI: 10.1007/s12035-018-0879-1
|View full text |Cite
|
Sign up to set email alerts
|

Parkin in Parkinson’s Disease and Cancer: a Double-Edged Sword

Abstract: Parkin for more than a decade has been portrayed as a neuroprotector gene is now increasingly emerging as a multifaceted gene that can exert entirely opposite effects i.e., both cell proliferation and apoptosis. Parkinson's disease, a neurological disease, progresses due to excess in cell death, while, in case of cancer, cell death normally fails to occur. Parkin, an E3 ubiquitin ligase, was first identified as a gene implicated in autosomal recessive juvenile Parkinsonism, but several evidences indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 118 publications
0
37
0
Order By: Relevance
“…Furthermore, the role of parkin in promoting the mitochondria biogenesis has been demonstrated in neuronal cells and in the brain of living animals 67,68 , and the conditional knockout of parkin results in the loss of mitochondria and resulting neuronal degeneration 68 . HeLa cells used in this study have been derived from cervical cancer cells and lack parkin, as do many cancer cells, in which parkin acts as a tumor suppressor 69,70 . We show that Mdm2 enhances parkin's ligase activity and parkin-dependent ubiquitination of mitofusin-1, one of the key regulators of mitophagy 71 .Thus, the most straightforward interpretation of the evidence is that Mdm2 facilitates parkin-dependent mitophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the role of parkin in promoting the mitochondria biogenesis has been demonstrated in neuronal cells and in the brain of living animals 67,68 , and the conditional knockout of parkin results in the loss of mitochondria and resulting neuronal degeneration 68 . HeLa cells used in this study have been derived from cervical cancer cells and lack parkin, as do many cancer cells, in which parkin acts as a tumor suppressor 69,70 . We show that Mdm2 enhances parkin's ligase activity and parkin-dependent ubiquitination of mitofusin-1, one of the key regulators of mitophagy 71 .Thus, the most straightforward interpretation of the evidence is that Mdm2 facilitates parkin-dependent mitophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it is observed that Parkin influences the expression of the VEGF receptor (VEGFR). In Parkin cells, expression of VEGFR is found to be reduced when compared with controls (Kerbel and Kamen, 2004;Sherwood et al, 1971;Wahabi et al, 2018;Waltenberger et al, 1994), through an unknown mechanism.…”
Section: Parkinson's Diseasementioning
confidence: 98%
“…Ample evidence suggests that Parkin is a tumor suppressor gene, involved in a variety of cancers (Cesari et al, 2003;Denison et al, 2003;Picchio et al, 2004;Wahabi et al, 2018;Wang et al, 2004). Parkin is an E3 ubiquitin-protein ligase, which ubiquitinates a large number of proteins, including itself, to promote different pathways, including ubiquitin -proteasomal pathway, and mitophagy.…”
Section: Parkinson's Diseasementioning
confidence: 99%
See 2 more Smart Citations